Effect of Chloride Salt on Reinforced Concrete Structures - Naji Hilal, Nahla (Anbar Journal of Engineering Sciences, 2012)
The corrosion of reinforcement iron is one of the dangerous problems in middle and west of Iraq and Arabian gulf which is needed to large investigations because of increasing of chloride salts in soil and ground water and rising of temperature at summer which encourage of finding the shrinkage cracks in their two types : Plastic and drying shrinkage . cracks are easy way for harmful ions present at soil and ground water to enter through reinforced concrete making damage for protection film a rounding rein forced iron and led to rust with cracks in concrete cover a rounding rein forced iron added to its may be to cause structural damage in members of rein forced concrete because of absence of a adhesive between concrete and steel leading to structural failure . This research presents study for this problem and knowing their causes and methods to reduce it. Experimental work show that the concrete exposed to chlorides leads to decreasing in density with ratio (1.5%) and decreasing in flextural strength with ratio (138%) at age (28) day .